2015
DOI: 10.1128/jcm.00313-15
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a gp60-Based Typing Assay for Cryptosporidium viatorum

Abstract: The apicomplexan intestinal parasites of the genus Cryptosporidium take a major toll on human and animal health and are frequent causes of waterborne outbreaks. Several species and genotypes can infect humans, including Cryptosporidium viatorum, which, to date, has only been found in humans. Molecular characterization of Cryptosporidium spp., critical to epidemiological analyses, is commonly based on gp60 gene analysis, which appears to require bespoke species-or group-specific PCR primers due to extensive gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 21 publications
(41 reference statements)
1
63
1
Order By: Relevance
“…The two C. ubiquitum subtypes found in this study belong to two novel subtype families (21), and the C. viatorum subtype (XVaA6) found in this study has not been reported elsewhere (8). In phylogenetic analysis of gp60 sequences, the new C. ubiquitum subtype families formed a cluster with the rodent subtype families XIIb, XIIc, and XIId rather than the ruminant subtype family XIIa.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The two C. ubiquitum subtypes found in this study belong to two novel subtype families (21), and the C. viatorum subtype (XVaA6) found in this study has not been reported elsewhere (8). In phylogenetic analysis of gp60 sequences, the new C. ubiquitum subtype families formed a cluster with the rodent subtype families XIIb, XIIc, and XIId rather than the ruminant subtype family XIIa.…”
Section: Discussionmentioning
confidence: 74%
“…However, it is becoming an important Cryptosporidium species in humans in industrialized nations (21,22), although it has been reported in only a few human cases in developing countries (21,23,24). In contrast, C. viatorum is known as a human pathogen in developing countries, as human infections in the United Kingdom and Sweden have been linked to travels to India, Pakistan, Bangladesh, Kenya, Barbados, and Guatemala (8). However, its presence in developing countries has been confirmed only in Ethiopia and Nigeria (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One common target used in subtyping of these species is the 60-kDa glycoprotein (gp60) gene, as it is highly polymorphic and divides the two Cryptosporidium species into several major subtype families (Strong et al, 2000). In recent years, subtyping tools based on gp60 sequences have been developed for other Cryptosporidium species and genotypes such as C. meleagridis , C. ubiquitum , C. fayeri , C. viatorum , and Cryptosporidium chipmunk genotype I (Guo et al, 2015; Li et al, 2014; Power et al, 2009; Stensvold et al, 2014; Stensvold et al, 2015). With the availability of whole genome sequences, some of the new tools, such as the one for Cryptosporidium chipmunk genotype I, have used conserved nucleotide sequences in PCR primer design (Guo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%